ANALYSIS OF THE MAIN CAUSES OF TRANSFORMER DAMAGE - G. N. Mustafakulova (European Science Publishing, 2023)
The permissible values of the operating factors and their number depend on the operating time of the transformer. The operational reliability of transformer equipment is directly related to its service life. The increasing nature of the transformer damage curve with time (or the "life curve" of a particular transformer) after it has reached its rated service life is similar to similar: the dependence of aging of all types of electrical equipment. The main feature of transformer equipment is that the service life is largely determined by the condition of oil-paper insulation in the process of its natural temporary aging and under the influence of external factors.
Keywords: transformer, operation, reliability, power, load, network, disadvantages of operation, repair defects, climatic and external influences.